2010
DOI: 10.1099/vir.0.025247-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiviral activity against herpes simplex virus in the abalone Haliotis laevigata

Abstract: As viruses are extremely abundant in oceans, marine organisms may have evolved novel metabolites to protect themselves from viral infection. This research examined a well-known commercial gastropod, abalone (Haliotidae), which in Australia have recently experienced disease due to a neurotropic infection, abalone viral ganglioneuritis, caused by an abalone herpesvirus (AbHV). Due to the lack of molluscan cell lines for culturing AbHV, the antiviral activity of the abalone Haliotis laevigata was assessed against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 70 publications
0
39
0
1
Order By: Relevance
“…Haemocyanins are copper containing glycoproteins and a major haemolymph component, approximately 50 % to w90 %, of some mollusc species (Coates & Nairn, 2014). Abalone haemocyanin inhibits HSV-1 infection of Vero cells, presumably by blocking viral entry (Dang et al, 2011;Zanjani et al, 2014). The anti-HSV-1 activity of abalone plasma does not increase above baseline levels in response to experimental infection with AbHV (Dang et al, 2013).…”
Section: Antiviral Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Haemocyanins are copper containing glycoproteins and a major haemolymph component, approximately 50 % to w90 %, of some mollusc species (Coates & Nairn, 2014). Abalone haemocyanin inhibits HSV-1 infection of Vero cells, presumably by blocking viral entry (Dang et al, 2011;Zanjani et al, 2014). The anti-HSV-1 activity of abalone plasma does not increase above baseline levels in response to experimental infection with AbHV (Dang et al, 2013).…”
Section: Antiviral Compoundsmentioning
confidence: 99%
“…Investigations into the antiviral activity of molluscan AMPs and tissue homogenates is hampered by the lack of continuous cell lines from marine molluscs (Yoshino et al, 2013) and the fact that OsHV-1 cannot be cultured in primary cell cultures from bivalves (details in Garcia et al, 2011). Numerous studies have therefore utilized a heterologous model involving HSV-1 and African green monkey kidney (Vero) cells to identify antiviral compounds in tissue homogenates from commercially important bivalves (Carriel-Gomes et al, 2006;Defer et al, 2009;Green et al, 2014c;Olicard et al, 2005a, b;Segarra et al, 2014a;Zeng et al, 2008) and gastropods (Dang et al, 2011;Zanjani et al, 2014).…”
Section: Antiviral Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have shown that plasma of abalone haemolymph also contains antiviral 100 compounds using the plaque assay for HSV-1 (Dang et al 2011 …”
mentioning
confidence: 99%